PENGARUH PENGGUNAAN MEDIA LEAFLET TERHADAP SIKAP IBU TENTANG STUNTING DI PUSKESMAS PETALING - -, Sri Hastini Jaelani; Savita, Riza (JURNAL SMART ANKes, 2024)
Stunting is a chronic condition that hinders children's growth due to prolonged malnutrition. Stunting not only inhibits physical development but also threatens cognitive development, ultimately reducing a child's productivity in adulthood. This study aims to determine the effect of education using leaflet media on mothers' attitudes toward stunting incidence in the Petaling Public Health Center area. This study employs a pre-experimental research method with a one-group pretest and post-test design. The sample consists of 38 mothers with toddlers in the working area of the Pangkal Pinang Public Health Center, selected through purposive sampling. Data analysis was conducted using the Wilcoxon test. The results show that the average mothers' attitude score before receiving education through leaflets was 29.66, which increased to 34.03 after the intervention. This indicates that education using leaflet media influences mothers' attitudes toward stunting incidence at the Petaling Public Health Center in Pangkal Pinang, as evidenced by the Wilcoxon test analysis with a p-value of 0.000 < 0.05. It is expected that the findings of this study on stunting education using leaflet media can serve as a reference for future researchers who wish to conduct further studies on mothers' attitudes toward stunting incidence. Keywords: Leaflet Media, Mothers' Attitudes, Stunting.